2021
DOI: 10.1177/16878140211067011
|View full text |Cite
|
Sign up to set email alerts
|

Deep reinforcement learning-based rehabilitation robot trajectory planning with optimized reward functions

Abstract: Deep reinforcement learning (DRL) provides a new solution for rehabilitation robot trajectory planning in the unstructured working environment, which can bring great convenience to patients. Previous researches mainly focused on optimization strategies but ignored the construction of reward functions, which leads to low efficiency. Different from traditional sparse reward function, this paper proposes two dense reward functions. First, azimuth reward function mainly provides a global guidance and reasonable co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Jin et al [ 9 ] have demonstrated the efficacy of DRL in improving post-stroke limb function, whereas Majhi and Kashyap [ 10 ] have explored adaptive algorithms for patient-specific therapy adjustments. Furthermore, the work by Wang et al [ 11 ] has been instrumental in showcasing how DRL can optimize engagement levels during robotic-assisted therapy. These studies underscore the potential of DRL to enhance the adaptability and personalization of rehabilitation protocols according to motor rehabilitation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Jin et al [ 9 ] have demonstrated the efficacy of DRL in improving post-stroke limb function, whereas Majhi and Kashyap [ 10 ] have explored adaptive algorithms for patient-specific therapy adjustments. Furthermore, the work by Wang et al [ 11 ] has been instrumental in showcasing how DRL can optimize engagement levels during robotic-assisted therapy. These studies underscore the potential of DRL to enhance the adaptability and personalization of rehabilitation protocols according to motor rehabilitation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We saw how deep reinforcement learning is still poorly investigated even if in other fields has been shown to surpass classical reinforcement learning. In particular deep reinforcement learning provides a new solution for rehabilitation robot trajectory planning and control strategies with a high accuracy (Wang et al, 2021a). Given the high quantity of algorithms available the choice strictly depends on the given problem (Arulkumaran et al, 2017).…”
Section: Reinforcement Learningmentioning
confidence: 99%